Correlations of adherence to iron supplements and prevalence of anemia in antenatal women - Sajith, Manjusha; Nimbargi, Vandana; Shah, Sejal; Tekawade, Srushti; Agiwale, Jayesh; Pawar, Atmaram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The prevalence of anemia in pregnant women has remained unacceptably high worldwide despite the fact that routine iron supplementation during pregnancy has been almost universally recommended to prevent maternal anemia. The major problem with iron supplementation during pregnancy is compliance. The objective of this study was to correlate iron supplements compliance among pregnant women and incidence of anemia during pregnancy. Methods: A Prospective observational study was conducted over a period of nine months from August 2015 to April 2016 in the department of obstetrics and gynecology, Bharati Hospital and Research Center, Pune. Pregnant women more than 14 weeks who attended antenatal care unit were enrolled in this study. Data for compliance was collected by two methods - first by personal interview as well as looking for the empty iron tablet strips. Pregnant women were followed till the date of delivery and maternal outcome were noted. Results: Our results show that 64% were strictly compliant, 33% with partially complaint and 3% with non-complaint with iron supplements. The mean Hemoglobin concentration of pregnant women who strictly complies with iron supplements were 11.6 g/dl where the non-compliant and partially complaint to iron supplements were 9.7 g/dl. The prevalence of anemia was found to be more in partial and non-compliant to iron supplements (13% p value <0.001). Conclusions: Anaemia, low haemoglobin levels were found more in non-complaint and partially complaint pregnant women. The findings from our study highlighted that antenatal health and a nutritional intervention program for pregnant women is needful.